Kepercayaan Bulan Suro, Pernikah PANDANGAN HUKUM ISLAM TERHADAP EKSISTENSI KEPERCAYAAN ADAT JAWA DALAM PERNIKAHAN BULAN SURO: Pada Masyarakat Muslim Desa Keras Kecamatan Diwek Kabupaten Jombang - Della, Della Ika Ayuningtyas; Afif , Abdullah (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2024)
This thesis aims to find out the review of Islamic law in Javanese customary beliefs towards the marriage of the Moon of Suro. The author will explain how the public views the marriage belief of the month of Suro, how Islamic law views the belief, and how the impact if it continues to carry it out. This research is a qualitative field research with an empirical normative approach. The author uses data analysis techniques in the form of objective interpretations. Conclusion of the study For the community to be more careful in carrying out things or things related to worship, by straightening intentions or returning everything to God alone. Because intention is a very important capital in carrying out something. People must be aware that customary law is a human product while God's law is a provision that comes from God, so customary law cannot be used as a guide in every problem resolution. In the application of Islamic law, it must prioritize the welfare of the people, as stated in the theory of 'urf, so this needs to be studied more deeply so as not to cause confusion among Muslims, especially the Javanese Muslim community who will carry out the Suro Moon wedding. Keyword : Suro Moon Beliefs, Javanese Marriage, Islamic Law.